Catalytic Oxidation of β‐Keto Esters by Manganese(III)/ Cobalt(II) and Consecutive Cyclization to Heterocycles. Issue 14 (1st August 2014) - Ju, Yeming; Miao, Di; Seo, Jeong Gil; Koo, Sangho
Abstract The manganese(III)‐mediated oxidation of β‐keto esters becomes catalytic by the addition of a second cobalt(II) oxidant. This radical‐initiated oxidation of β‐keto esters is general under aerobic condition to produce α‐oxo esters, which may consecutively undergo further heterocyclizations, either by intramolecular Diels–Alder reaction to dihydropyrans or by aromatic cyclization to furans depending upon the substitution pattern at the δ‐carbon. Since acetoacetates are very useful in carbon‐carbon bond formation with allylic halides to give various β‐keto esters, this one‐pot catalytic oxidation and heterocyclization provides an efficient repertoire for the construction of diverse heterocyclic compounds. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>